Peran Pengetahuan Pendahulu dan Kepekaan terhadap Kemampuan Mengidentifikasi Peluang Usaha Mikro Pedesaan - Muhammad Setiawan Kusmulyono (Jurnal Manajemen Maranatha, 2016)
Opportunity identification skills is important element in determining the success of a venture. Good opportunity identification skills will be a key success factors in optimizing gap that existed in the market. Through a micro enterprisesdevelopment program that run by Prasetiya Mulya University, researcher tried to analyze the relations of prior knowledge and alertness to the opportunity identification skills of the students.Keywords: Opportunity Identification, Students, Alertness, Prior Knowledge